A new target ligand Ser–Glu for PEPT1-overexpressing cancer imaging - Dai TC (Dove Medical Press, 2016)
Tongcheng Dai,1 Na Li,1 Lingzhi Zhang,1 Yuanxing Zhang,1,2 Qin Liu1,2 1State Key Laboratory of Bioreactor Engineering, East China University of Science and Technology, 2Shanghai Collaborative Innovation Center for Biomanufacturing Technology, Shanghai, People’s Republic of China Abstract: Nanoparticles functionalized with active target ligands have been widely used for tumor-specific diagnosis and therapy. The target ligands include antibodies, peptides, proteins, small molecules, and nucleic acid aptamers. Here, we utilize dipeptide Ser–Glu (DIP) as a new ligand to functionalize polymer-based fluorescent nanoparticles (NPs) for pancreatic cancer target imaging. We demonstrate that in the first step, Ser–Glu-conjugated NPs (NPs-DIP) efficiently bind to AsPC-1 and in the following NPs-DIP are internalized into AsPC-1 in vitro. The peptide transporter 1 inhibition experiment reveals that the targeting effects mainly depend on the specific binding of DIP to peptide transporter 1, which is remarkably upregulated in pancreatic cancer cells compared with varied normal cells. Furthermore, NPs-DIP specifically accumulate in the site of pancreatic tumor xenograft and are further internalized into the tumor cells in vivo after intravenous administration, indicating that DIP successfully enhanced nanoparticles internalization efficacy into tumor cells in vivo. This work establishes Ser–Glu to be a new tumor-targeting ligand and provides a promising tool for future tumor diagnostic or therapeutic applications. Keywords: imaging, pancreatic cancer, PEPT1 transporter, Ser–Glu, target ligand